2019
DOI: 10.12659/msm.914343
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Mean Platelet Volume in Patients with AA Amyloidosis and AA Amyloidosis Secondary to Familial Mediterranean Fever: A Retrospective Chart – Review Study

Abstract: Background Amyloidosis is a protein-misfolding disease characterized by the deposition of aggregated proteins in the form of abnormal fibrils that disrupt tissue structure, ultimately causing disease. Amyloidosis is very frequent in untreated familial Mediterranean fever (FMF) patients and it is the most important feature that determines the prognosis of FMF disease. The mean platelet volume (MPV) in FMF has been previously studied. However, whether MPV level in FMF patients is lower or higher com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…AA aggregates then progressively disrupt tissue integrity and ultimately impair the physiological function of affected organs. Furthermore, patients with systemic AA amyloidosis may exhibit altered red blood cell and platelet volumes 43, 44 , which in turn can activate inflammasomes and boost the inflammasome capacity of macrophages, neutrophils and monocytes 45 . We therefore assessed the cellular composition of the spleen and of peripheral blood at baseline and after induction of experimental AA amyloidosis in Pycard +/+ and Pycard -/- mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…AA aggregates then progressively disrupt tissue integrity and ultimately impair the physiological function of affected organs. Furthermore, patients with systemic AA amyloidosis may exhibit altered red blood cell and platelet volumes 43, 44 , which in turn can activate inflammasomes and boost the inflammasome capacity of macrophages, neutrophils and monocytes 45 . We therefore assessed the cellular composition of the spleen and of peripheral blood at baseline and after induction of experimental AA amyloidosis in Pycard +/+ and Pycard -/- mice.…”
Section: Resultsmentioning
confidence: 99%
“…Once present, AA aggregates progressively disrupt tissue integrity and ultimately impair physiological function of affected organs. Furthermore, patients with systemic AA amyloidosis may also exhibit altered red blood cell and platelet volumes according to recent reports (40,41). Moreover, the presence of platelets in the circulation and platelet-derived enhancing factors supply inflammasome activation and boost inflammasome capacity of macrophages, neutrophils and monocytes in inflammation (42).…”
Section: Splenic Architecture and Peripheral Blood In Aa Amyloidosismentioning
confidence: 97%
“…In another study Sakalli et al reported higher MPV in patients with proteinuria compared to patients without proteinuria however authors did not specifically disclose MPV levels in patients with and without AA amyloidosis [7]. In a small sample size study investigating the effect of renal function on MPV in AA amyloidosis, no significant relationship was found between MPV and GFR [13]. In our study with the largest sample size that included 124 AA amyloidosis patients and a total of 703 patients with glomerulonephritis, we did not observe a correlation between MPV and proteinuria or renal function in AA amyloidosis group and in whole study population.…”
Section: Discussionmentioning
confidence: 96%
“…However, there are discrepancies among the results of the studies. Although most of the studies revealed higher MPV levels in FMF patients compared to the control group [7][8][9][10][11][12], some other studies reported similar [13,14] or even lower MPV levels in FMF patients [15,16].…”
Section: Introduction Familialmentioning
confidence: 93%
“…Recent studies have highlighted the critical role of platelets in inflammation [2][3][4][5]. Activated platelets and platelet-derived microparticles by various factors can play an important role in inflammation by stimulating proinflammatory substances such as chemokines, cytokines, and nitric oxide [2].…”
Section: Introductionmentioning
confidence: 99%